(untitled) (Polifonia, 2016)
I invited Mervyn who kindly answered some questions about Roy and the philosophy of critical realism. Iam very grateful for this opportunity to have this interview. He is founding editor of Journal of Critical Realism and editor and principal author of Dictionary of Critical Realism. He recently completed a series of introductions to new Routledge editions of all Roy Bhaskar’s solo-authored books. He taught history and philosophy of the social sciences for many years at the University of Sydney and Macquarie University. He is now retired and lives in London.